The status of part-time employment among students at Binh Duong university – Ca Mau campus - Nguyen , Thuỳ Ngân; Nguyen , Xuân Nghi; Nguyen , Văn Mạnh (Tạp Chí Khoa Học Và Công Nghệ Trường Đại Học Bình Dương, 2025)
This study analyzes the current situation of part-time employment among business administration students at Binh Duong University, Ca Mau Campus. The research identifies three primary reasons driving students to take part-time jobs: financial pressure, the desire to gain practical experience, and the aspiration for independence. However, it also highlights challenges faced by students in balancing work and studies, including negative impacts on academic performance, time pressure, and potential risks. Based on these findings, the research team proposes solutions to help students balance their studies and part-time employment. These solutions include setting clear goals, managing time effectively, and choosing suitable jobs.